Atividade antibacteriana de óleo essencial de orégano (Origanum vulgare): ações in vitro e in situ para preservação de alimento - Cattelan, Marília Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Due to the incidence of foodborne illnesses and the increasing interest in the use of natural preservatives to replace chemical additives, this research aimed to evaluate in vitro and in situ effects of oregano essential oil (OEO), used individually and in combination with salt (sodium chloride) against two foodborne pathogens, Escherichia coli (ATCC 8739) and Staphylococcus aureus (ATCC 25923). It was employed a commercial sample of oregano essential oil (Origanum vulgare L.), which was characterized by gas chromatography. The in vitro antibacterial assays were conducted by the disc diffusion method. Microbial counts were standardized to 108 CFU.mL-1. The effect of OEO and salt was evaluated in factorial design 22 with a central point. For the in situ study was proposed as food system a oregano salad dressing, composed of powdered whole milk, water, vegetable soybean oil, soybean powder extract, OEO and salt. The latter two constituents were factors whose levels were evaluated. For this, it was used a central composite design with four factorial points, four axial points and three repetitions of the central point. Sensory assessment of salad dressing with OEO was evaluated in relation to the following attributes: appearance, aroma, consistence, flavour and overall acceptability. A nine point hedonic scale was employed, besides purchase intent by a structured five point scale. Chromatographic characterization of OEO revealed that the oil was composed mainly of carvacrol (65.1 %) and ρ-cymene (12.0 %). There was no significant difference in the acceptance of the samples (P < 0.05). Cluster analysis showed that formulation with intermediate quantities of salt and OEO was preferred by the judges. Oregano essential oil salad dressings with low salt content, regardless of OEO amount, presented higher intention to purchase. The distinctive oregano salad dressings formulations showed similar profiles, especially lipids present in levels from ...

Em virtude da incidência de doenças veiculadas por alimentos e do interesse crescente no emprego de conservantes naturais para substituir os aditivos químicos, esta pesquisa objetivou avaliar os efeitos in vitro e in situ do óleo essencial de orégano (OEO), empregado individualmente e em combinação com sal (cloreto de sódio), sobre duas bactérias contaminantes de alimentos, Escherichia coli (ATCC 8739) e Staphylococcus aureus (ATCC 25923). Para tanto, empregou-se uma amostra comercial de óleo essencial de orégano (Origanum vulgare L.), que foi caracterizada por cromatografia gasosa. Os ensaios de resistência in vitro foram efetuados por meio do procedimento de difusão em ágar por disco. A contagem microbiana foi padronizada em 108 UFC.mL-1. O efeito do OEO e do sal foi avaliado em planejamento fatorial 22 com um ponto central. Para o estudo in situ foi proposto como sistema alimentício um condimento preparado de orégano, composto por leite em pó integral, água, óleo vegetal de soja, extrato de soja em pó, OEO e sal, sendo os dois últimos constituintes os fatores cujos níveis foram avaliados. Para tanto, empregou-se um delineamento composto central rotacional, com 4 pontos fatoriais, 4 pontos axiais e 3 repetições do ponto central. A aceitação sensorial dos condimentos formulados com diferentes quantidades de OEO e de sal foi avaliada em relação aos seguintes atributos sensoriais: aparência, aroma, textura, sabor e aceitação global, empregando uma escala hedônica de nove pontos. A intenção de compra foi pesquisada por uma escala de cinco pontos estruturada. As distintas formulações do condimento preparado de orégano foram avaliadas centesimalmente por meio de análises dos teores de cinzas, lipídeos, proteínas e umidade. A caracterização cromatográfica do OEO revelou que o produto composto majoritariamente por carvacrol (65,1 %) e ρ- cimeno (12,0 %). Não houve diferença significante na aceitação das...
Keywords: Tecnologia de alimentos; Alimentos - Microbiologia; Orégano; Essencias e oleos essenciais; Anti-infecciosos; Alimentos - Avaliação sensorial; Food technology